PERANAN PEMUSIK GEREJA DALAM MENGIRINGI NYANYIAN JEMAAT - Frisilia Durikase; Behreme Adyatmo Purba (Clef: Jurnal Musik dan Pendidikan Musik, 2020)
Abstract This paper is intended to describe the musical mastery of church musicians or worship attendants. The accompanist who truly mastered the technique or pattern of accompanying songs in congregational worship and integrating with the musical instruments used is a beautiful harmony for church singing. This paper uses a descriptive method that is a research method aimed at phenomena that exist today or in the past, and this descriptive method by looking at the reality that occurs in a church caused by a musician. (1) Lack of insight in song mastery, (2) Lack of insight in using appropriate accompaniment patterns, (3) Lack of practice before meeting in worshiping, (4) Lack of relationships and communication between religious leaders and musicians.